Integrated weed management in vegetable crops - Dubey, R. P. (Indian Farming, 2018)
Frequent irrigations and application of farmyard manure and fertilizers induces heavy infestation of weeds in vegetable crops and reduce the crop yields drastically. The critical period of crop-weed competition varies from 15 to 30 days in okra and between 30 and 70 days in onion. Cultural methods such as manual weeding, stale seed-bed technique, mulching, soil solarization in vegetable nurseries, drip irrigation etc. help in reducing weed problem. Integration of pre-emergence herbicides with intercultural operations (hoeing, earthing-up, mulching) has been found effective and economical.